Testing As Commodification - Katharine B. Silbaugh (Washington University Journal of Law & Policy, 2011)
In this Essay, the author addresses criticism of the testing movement by education experts such as Jonathan Kozol. She explores the similarities in the discourses of philosophical discussions of commodification and behavioural economic discussions of intrinsic motivations. One conclusion that the author draws is that the comparison between the testing movement and commodification literature is not perfect, but they have both been counted, compared and measured, and flattened or thinned out of values.
Keywords: Commodification; Educational change; Education & state; School choice; Law & behavioral economics